"Ada Kuis di Tengah Gempa”: Membangun Epistemologi Liputan Bencana di Media - Iwan Awaluddin Yusuf (Jurnal Komunikasi, 2006)
In the disaster prone area such as Indonesia, the strategic role of the media to educate public become a must Regular information that provided by media will be like an early warning system to the society and remind them that they are in the disaster prone area so that they have to be ready to face it The media won't be able to prevent the disaster, but they still can contribute in preventing too many victims by reducing panic society because of the irresponsible rumors and issues. This article deals with: first, disaster epistemology, disaster relations with human and nature; second, snapshot the practice of disaster media reporting in Indonesia -particularly television- and also media role in building information agenda setting related to disaster; third, in the end of the essay will try to formulate the important role of the media in public education process about how to face disaster proportionally and make the media as part of the early warning system that needed in the future.